Poorer maternal diet quality and increased birth weight*. (18th June 2018) - Grandy, Madeline; Snowden, Jonathan M.; Boone-Heinonen, Janne; Purnell, Jonathan Q.; Thornburg, Kent L.; Marshall, Nicole E.
Abstract: Objective: Maternal diet and gestational weight gain (GWG) influence birth weight and infant adiposity, which are important predictors of lifetime health. To better understand these relationships, we studied associations between maternal diet and GWG, adiposity, and birth weight in a well characterized cohort of pregnant women. Study design: Data were obtained from 41 term (>37 weeks), uncomplicated, singleton pregnancies according to pre-pregnancy BMI categories of normal ( n = 11), overweight ( n = 15), or obese ( n = 15). Daily consumption of protein, fat, and carbohydrates and a Healthy Eating Index (HEI-2010) score were determined from 24 h food recall collections. Associations were modeled using multinomial logistic and linear regression. Results: Neither the third trimester maternal diet quality nor the macronutrient consumption was associated with GWG after adjusting for pre-pregnancy BMI, maternal age, and parity. A ten-point lower HEI-2010 score was associated with 200 g higher infant birth weight and a 1.0 cm longer length. However, maternal HEI-2010 and macronutrient composition were unrelated to infant percent body fat, ponderal index, or abdominal circumference. Conclusions: Poorer third trimester maternal diet quality was associated with higher birth weight and longer length, but was unrelated to markers of infant adiposity. GWG was independent of third trimester maternal diet composition and quality.